2010
DOI: 10.1063/1.3430987
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-vacancy-related high-temperature dielectric relaxation in SrTiO3 ceramics

Abstract: Oxygen-vacancy-related dielectric relaxations in SrTiO3 at high temperatures J. Appl. Phys. 113, 094103 (2013); 10.1063/1.4794349 Structure, magnetic and dielectric properties in Mn-substituted Sm1.5Sr0.5NiO4 ceramics J. Appl. Phys. 110, 064110 (2011); 10.1063/1.3639282Oxygen-vacancy-related dielectric relaxation in SrBi 2 Ta 1.8 V 0.2 O 9 ferroelectrics Quantum paraelectric SrTiO 3 has resulted in many investigations because of the anomalous properties. Here, using the conventional solid-state reaction method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(38 citation statements)
references
References 35 publications
5
32
0
Order By: Relevance
“…For PLT20 and PLT32 ceramic, activation energies are about 1.73 and 1.75 eV respectively. For all compositions, values of activation energies are very close to OVs related high temperature dielectric relaxations in perovskite systems, such as: SrTiO 3 44 , (PbLa)(Zr 0.9 Ti 0.1 )O 3 45 , and (Pb,Cd,La)TiO 3 ceramics 42 .
Figure 4Normalized imaginary parts Z ″ /Z ″ max of impedance as a function of frequencies for ( a ) PLT20, ( b ) PLT24, ( c ) PLT28 and ( d ) PLT32 ceramics.
Figure 5ln ω versus 1000/T curves for PLT ceramics, straight lines are used to fit the Arrhenius law.
…”
Section: Resultssupporting
confidence: 56%
“…For PLT20 and PLT32 ceramic, activation energies are about 1.73 and 1.75 eV respectively. For all compositions, values of activation energies are very close to OVs related high temperature dielectric relaxations in perovskite systems, such as: SrTiO 3 44 , (PbLa)(Zr 0.9 Ti 0.1 )O 3 45 , and (Pb,Cd,La)TiO 3 ceramics 42 .
Figure 4Normalized imaginary parts Z ″ /Z ″ max of impedance as a function of frequencies for ( a ) PLT20, ( b ) PLT24, ( c ) PLT28 and ( d ) PLT32 ceramics.
Figure 5ln ω versus 1000/T curves for PLT ceramics, straight lines are used to fit the Arrhenius law.
…”
Section: Resultssupporting
confidence: 56%
“…reported that a large electro-shape-memory effect (up to 0.23% under the electric field of 5 kV/mm) in Mn-doped (Pb,Sr)TiO 3 ceramics10. SrTiO 3 is a quantum paraelectric and shows dielectric relaxation at high temperatures due to oxygen vacancies20212223. While in this work, both dielectric relaxations and pinning/depinning phenomenons were observed in (Sr,Pb)TiO 3 ceramics.…”
mentioning
confidence: 48%
“…Recently, the research about oxygen vacancies in materials has been done from theory and experiment451215213536373839404142. Li et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that dielectric relaxation in oxide materials in high temperature region are usually related to OVs, and oxygen-vacancy-related dielectric relaxation appears typically in the low-frequency region. [22][23][24] Obviously, OVs are a key factor to understand many properties in the high temperature region, and understanding the dynamic mechanism of OVs is of vital importance. Previous work on PZT95/5 based materials mainly focused on depolarization mechanisms, 14 electrocaloric effect, 11 etc.…”
Section: Introductionmentioning
confidence: 99%